Effect of Using the Computer in Teaching Physics to the Fifth Secondary Grade on the Achievement of Students and Their Retention of Information - AI- Hisnawi, M. A.A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aims of research is to know the effect of using the computer inteaching physics to the fifth secondary grade on the achievement of the students and their retention of  information .The sample consists of ( 50 ) students in the fillh secondary grade (scicnti fie  branch  )   in  Nassiriyah   secondary  school   in  Thi-qar governorate in ( 200 I - 2002 ) that chooses as random Iy and dividedto t>vo equivalent groups:control and experimental .The researcher built the teaching plans of each group . The five lessons choice from curriculum , and desi b'Tl  five computer teaching programs , and final achievement test from multiple - choice type consists of ( 30) questions that has validity and reliability.The application of the research continued five weeks, were the control group teaching by traditional methods when the experimenta l group reaching by traditional methods plus computer teaching programs. After  that  we applied  the  final  achievement  test  andrepeated it after three weeks as a test of retention of information .The  percentage ,  t-test  and  person coloration coffient  used asstatisti cal methods .                                                                                                                                       'The findings of the research showed the supremacy of the students of experimental  group in achievement and retention of information tcslS on the students of the control group .